The Mediation Role of Motivation in Enhancing Performance: The Impact of Individual Characteristics and Compensation - Asat Asat; Arief Subyantoro (Journal of Islamic Economics Lariba, 2020)
This study aims to analyze the effect of Individual Characteristics, Compensation on the Performance of Extension Workers with Motivation as a Mediating Variable in the UPTD of the Agricultural and Fisheries Agricultural Counseling Center, Sleman, Yogyakarta. The object of this study is the Extension of the status of Civil Servants (PNS) in UPTD Food and Fisheries Agricultural Counseling Center, Sleman, Yogyakarta, amounting to 46 extension agents. This research was conducted in January 2020 - February 2020. Data collection techniques in this study used a questionnaire method. The analytical tool used is path analysis. Based on the analysis that has been done, the results are obtained that partially individual characteristics significantly influence the performance of the instructor at the UPTD Extension Service Center for Agriculture and Fisheries in Sleman Regency. Compensation has a significant effect on the performance of the instructor in the UPTD extension agent of the Sleman Regency Food and Fisheries Agricultural Counseling Center. There is a Positive Effect of Individual Characteristics on Performance Mediated by Motivation at the UPTD Agricultural and Fisheries Counseling Center, Sleman, Yogyakarta. And there is a Positive Effect of Compensation on Performance Mediated by Motivation at the UPTD of the Agricultural and Fisheries Agricultural Counseling Center, Sleman, Yogyakarta.Keywords: Individual Characteristics, Compensation, Performance, and Motivation.